Higher-Order Aberrations Following Ray Trace LASIK and the Impact of Eye Movement on Coma [Letter] - Ning J; Zhang L (Clinical Ophthalmology)
Jiliang Ning, Lijun Zhang Department of Ophthalmology, The Third People’s Hospital of Dalian, Dalian, People’s Republic of ChinaCorrespondence: Lijun Zhang, The Third People’s Hospital of Dalian, No. 40, Qianshan Road, Ganjingzi District, Dalian, Liaoning, People’s Republic of China, Email nhc20112814@163.com